2013
DOI: 10.1128/jcm.00572-13
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Analysis of Methicillin-Resistant and Methicillin-Susceptible Staphylococcus aureus Carriage in Healthy Adolescents

Abstract: bTo determine the long-term carriage patterns, strain relatedness, and incidence of subsequent infections among methicillinresistant Staphylococcus aureus (MRSA) and methicillin-susceptible S. aureus (MSSA) carriers, we screened 154 high school students for nasal carriage of S. aureus on 8 occasions over 11 months. Persistent carriage was defined as a positive culture on >7 occasions. Two consecutive isolates from the same subject comprised a pair, and strain relatedness was determined for each pair by molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 35 publications
(39 reference statements)
3
18
1
Order By: Relevance
“…Other studies from Europe showed similar colonization rates (Sakwinska et al, 2009;Lozano et al, 2011;Mehraj et al, 2014;Holtfreter et al, 2016). Similar or slightly elevated carriage rates were also reported in studies from Australia and several Asian countries (Munckhof et al, 2008;Chatterjee et al, 2009;Ma et al, 2011;Chen et al, 2013). Significantly higher rates were recorded in Southern European countries and the United States (up to 35%, Tavares et al, 2013;Champion et al, 2014).…”
Section: Methicillin-resistant Staphylococcus Aureus In General and Hsupporting
confidence: 69%
“…Other studies from Europe showed similar colonization rates (Sakwinska et al, 2009;Lozano et al, 2011;Mehraj et al, 2014;Holtfreter et al, 2016). Similar or slightly elevated carriage rates were also reported in studies from Australia and several Asian countries (Munckhof et al, 2008;Chatterjee et al, 2009;Ma et al, 2011;Chen et al, 2013). Significantly higher rates were recorded in Southern European countries and the United States (up to 35%, Tavares et al, 2013;Champion et al, 2014).…”
Section: Methicillin-resistant Staphylococcus Aureus In General and Hsupporting
confidence: 69%
“…A quarter of the mothers were defined as transient carriers, of which most carried S. aureus in only one or two carriage events. In line with previous studies, we observed strain persistence in our healthy adult population, (12, 17). MRSA was not isolated from any mother at any point throughout the year.…”
Section: Discussionsupporting
confidence: 93%
“…12 The t026 clone is also reported to be carried in healthy adolescents in a longitudinal surveillance in Taiwan and is considered to be a globally spread clone. 9 The t1081 clone has been predominantly found in long-term care facilities in hospitals in Hong Kong since 2005 as a member of ST45/ SCCmec IV or V. 11 t074 has been reported to be highly correlated to t037 and t421, which can be clustered together by PFGE typing and share an approximately 75% similarity in their spa sequence. 27 In summary, in this study, SCCmec type III, IV, and V were the major SCCmec subtypes in our MRSA isolates.…”
Section: Discussionmentioning
confidence: 98%